Current Status and Future Directions of Neuromonitoring With Emerging Technologies in Neonatal Care - Variane, Gabriel Fernando Todeschi; Camargo, João Paulo Vasques; Rodrigues, Daniela Pereira; Magalhães, Maurício; Mimica, Marcelo Jenné (Frontiers in Pediatrics, 2022)
Neonatology has experienced a significant reduction in mortality rates of preterm population and critically ill infants over the last decades. Now, the emphasis is adequately directed towards improving long-term neurodevelopmental outcomes and quality of life. Brain-focused care has emerged as a necessity. The creation of neonatal neurocritical care units, or Neuro-NICUs, provides strategies to reduce brain injury using standardized clinical protocols, methodologies, and provider education and training. Bedside neuromonitoring has dramatically improved our ability to provide assessment of newborns at high risk. Non-invasive tools, such as continuous electroencephalography (cEEG), amplitude-integrated electroencephalography (aEEG), and near-infrared spectroscopy (NIRS), allow screening for seizures and continuous evaluation of brain function and cerebral oxygenation at the bedside. Extended and combined uses of these techniques, also described as multimodal monitoring, may allow practitioners to better understand the physiology of critically ill neonates. Furthermore, the rapid growth of technology in the Neuro-NICU, along with the increasing use of telemedicine and artificial intelligence with improved data mining techniques and machine learning (ML), has the potential to vastly improve decision-making processes and positively impact outcomes. This article will cover the current applications of neuromonitoring in the Neuro-NICU, recent advances, potential pitfalls, and future perspectives in this field.